The interaction between central and peripheral immune systems in methamphetamine use disorder: current status and future directions - Sai Shi; Yiwen Sun; Guiying Zan; Min Zhao (Journal of Neuroinflammation)
Abstract Methamphetamine (METH) use disorder (MUD) is characterized by compulsive drug-seeking behavior and substantial neurotoxicity, posing a considerable burden on individuals and society. Traditionally perceived as a localized central nervous system disorder, recent preclinical and clinical studies have elucidated that MUD is a multifaceted disorder influenced by various biological systems, particularly the immune system. Emerging evidence suggests that both central and peripheral immune responses play a crucial role in the initiation and persistence of MUD. Conceptualizing it as a systemic immune process prompts significant inquiries regarding the mechanisms of communication between peripheral and central compartments. Also, whether this intercommunication could serve as diagnostic biomarkers or therapeutic targets. This review begins by offering an overview of mechanistic studies pertaining to the neuroimmune and peripheral immune systems. Finally, future directions are suggested through the integration of innovative technologies and multidimensional data to promote the translation of basic mechanistic research into clinical diagnostic and therapeutic interventions.